1999
DOI: 10.1093/emboj/18.22.6552
|View full text |Cite
|
Sign up to set email alerts
|

The meiosis-specific recombinase hDmc1 forms ring structures and interacts with hRad51

Abstract: Eukaryotic cells encode two homologs of Escherichia coliRecA protein, Rad51 and Dmc1, which are required for meiotic recombination. Rad51, like E.coli RecA, forms helical nucleoprotein filaments that promote joint molecule and heteroduplex DNA formation. Electron microscopy reveals that the human meiosis-specific recombinase Dmc1 forms ring structures that bind single-stranded (ss) and double-stranded (ds) DNA. The protein binds preferentially to ssDNA tails and gaps in duplex DNA. hDmc1-ssDNA complexes exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 67 publications
(104 reference statements)
9
96
0
Order By: Relevance
“…The protein concentrations used in the experiments were 0 M (lanes 1, 5, 9, 13, 17, 21, 25, 29, and 33), 2 M (lanes 2, 6, 10, 14, 18, 22, 26, 30, and 34), 4 M (lanes 3, 7, 11, 15, 19, 23, 27, 31, and 35), and 8 M (lanes 4, 8, 12, 16, 20, 24, 28, 32, and 36). [6][7][8][10][11][12][14][15][16][18][19][20][22][23][24][26][27][28][30][31][32][34][35][36] (Ref. 36 and Fig.…”
Section: Tbpip/hop2 Enhances the Dmc1-mediated Homologous Pairingmentioning
confidence: 99%
“…The protein concentrations used in the experiments were 0 M (lanes 1, 5, 9, 13, 17, 21, 25, 29, and 33), 2 M (lanes 2, 6, 10, 14, 18, 22, 26, 30, and 34), 4 M (lanes 3, 7, 11, 15, 19, 23, 27, 31, and 35), and 8 M (lanes 4, 8, 12, 16, 20, 24, 28, 32, and 36). [6][7][8][10][11][12][14][15][16][18][19][20][22][23][24][26][27][28][30][31][32][34][35][36] (Ref. 36 and Fig.…”
Section: Tbpip/hop2 Enhances the Dmc1-mediated Homologous Pairingmentioning
confidence: 99%
“…Dmc1 was also proposed to be a structural and functional relative of RecA based on mutant and sequence analysis (Bishop et al 1992;Story et al 1993). Biochemical demonstration of recombinase activity for Rad51 and Dmc1 supports the idea that each protein promotes strand exchange by a mechanism related to that of RecA (Sung 1994;Baumann et al 1996;Li et al 1997;Masson et al 1999;Hong et al 2001). Although similar in several respects, electron microscopy (EM) analysis showed that Dmc1 and Rad51 differ in that Dmc1 has a strong tendency to form tori and can bind DNA in the toroid form Passy et al 1999;Kinebuchi et al 2004).…”
mentioning
confidence: 92%
“…The molecular activities of RAD51 and DMC1 proteins have been studied in depth in vitro. Both proteins form helical structures on ssDNA and mediate the invasion of those so-called presynaptic filaments into homologous duplex DNA to form displacement loops (Shinohara et al, 1992;Ogawa et al, 1993;Benson et al, 1994;Sung, 1994;Baumann et al, 1996;Li et al, 1997;Masson et al, 1999;Hong et al, 2001;Sehorn et al, 2004;Yu and Egelman, 2010). Although similar in structure, some differences between the two recombinases may exist.…”
Section: Introductionmentioning
confidence: 99%